-5j+76=8j-2

Simple and best practice solution for -5j+76=8j-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5j+76=8j-2 equation:


Simplifying
-5j + 76 = 8j + -2

Reorder the terms:
76 + -5j = 8j + -2

Reorder the terms:
76 + -5j = -2 + 8j

Solving
76 + -5j = -2 + 8j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-8j' to each side of the equation.
76 + -5j + -8j = -2 + 8j + -8j

Combine like terms: -5j + -8j = -13j
76 + -13j = -2 + 8j + -8j

Combine like terms: 8j + -8j = 0
76 + -13j = -2 + 0
76 + -13j = -2

Add '-76' to each side of the equation.
76 + -76 + -13j = -2 + -76

Combine like terms: 76 + -76 = 0
0 + -13j = -2 + -76
-13j = -2 + -76

Combine like terms: -2 + -76 = -78
-13j = -78

Divide each side by '-13'.
j = 6

Simplifying
j = 6

See similar equations:

| 4x-8=2(2x+2) | | 19-2x+4+x+19+x-1=34 | | 4x+7(1-x)=16 | | 5-4x+9=2x-10 | | y+5-2y=5y+3+2x | | 5x+6=3x+9 | | 28-4x=7-7x | | 10x-16=9x+2 | | 5(x+4)=3x+29 | | 4(x+2)-2=18 | | y-3.5=-21 | | -5j+78=8j-2 | | 3x-19=5x+2 | | 5-(2u-1)=14-4u | | x*2-2x=0 | | 3x-19=x-2 | | 2.23-3.14x=2x-4.195 | | 2(4x+3)=2 | | 4x-15=x+10 | | 5x-12=2x-9 | | 2H+4S=22 | | 5(x-3)=-13 | | 19-x+4+x+19+x-1=34 | | 3x=1.08 | | F(x)=(radx-2)-3 | | ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 |

Equations solver categories